Analysis of molecular and cellular bases of honey bee mushroom body development - Shuichi Kamata; Takeo Kubo; Hiroki Kohno (Scientific Reports)
Abstract In the honey bee, mushroom bodies (MBs), a higher-order center of the insect brain, comprise three class I Kenyon cell (KC) subtypes (lKC, mKC, and sKC) with distinct somata sizes and locations and gene expression profiles. While these KC subtypes have been suggested to function in different behavioral regulations, the molecular and cellular basis of their development remains obscure. Here, we showed that lKCs, mKCs, and sKCs are produced in that order at different pupal stages by labeling proliferating MB cells with 5-ethynil-2’-deoxyuridine at various pupal stages. RNA-sequencing analysis of FACS-sorted pupal MB cells identified genes that were upregulated in proliferating and non-proliferating MB cells, respectively. Furthermore, in situ hybridization of some of these genes labeled the proliferating cells or immature KCs in the MBs at pupal stages producing each subtype. We found that the expression patterns of SoxNeuro, optix, and asense were consistent with those in Drosophila MBs, while odd-paired, which functions in neuroblasts in Drosophila, was preferentially expressed in immature KCs in honey bees. Our findings revealed the basic scheme of the molecular and cellular processes of honey bee MB development and suggested that they are at least partially different from those of Drosophila MB development.